Mechanical heterogeneities in the subendothelial matrix develop with age and decrease with exercise. Issue 9 (14th June 2016) - Kohn, Julie C.; Chen, Adeline; Cheng, Stephanie; Kowal, Daniel R.; King, Michael R.; Reinhart-King, Cynthia A.
Abstract: Arterial stiffening occurs with age and is associated with lack of exercise. Notably both age and lack of exercise are major cardiovascular risk factors. While it is well established that bulk arterial stiffness increases with age, more recent data suggest that the intima, the innermost arterial layer, also stiffens during aging. Micro-scale mechanical characterization of individual layers is important because cells primarily sense the matrix that they are in contact with and not necessarily the bulk stiffness of the vessel wall. To investigate the relationship between age, exercise, and subendothelial matrix stiffening, atomic force microscopy was utilized here to indent the subendothelial matrix of the thoracic aorta from young, aged-sedentary, and aged-exercised mice, and elastic modulus values were compared to conventional pulse wave velocity measurements. The subendothelial matrix elastic modulus was elevated in aged-sedentary mice compared to young or aged-exercised mice, and the macro-scale stiffness of the artery was found to linearly correlate with the subendothelial matrix elastic modulus. Notably, we also found that with age, there exists an increase in the point-to-point variations in modulus across the subendothelial matrix, indicating non-uniform stiffening. Importantly, this heterogeneity is reversible with exercise. Given that vessel stiffening is known to cause aberrant endothelial cell behavior, and the spatial heterogeneities we find exist on a length scale much smaller than the size of a cell, these data suggest that further investigation in the heterogeneity of the subendothelial matrix elastic modulus is necessary to fully understand the effects of physiological matrix stiffening on cell function.